Alternativas de tratamento para hepatite viral crônica B: análise de custo-efetividade - Alessandra Maciel Almeida (2011)
Introduction: Hepatitis B is one of the most common infectious diseases worldwide and has been showing increasing expenditures in the Brazilian Unified Healh System (SUS). Objectives: To perform a pharmacoeconomic and epidemiological evaluation of interferon and lamivudine classified as high costs in SUS and utilized for the treatment of adults with chronic hepatitis B (CHB). Conduct a systematic review to evaluate the efficacy of interferon (conventional and pegylated) and lamivudine for the treatment of CHB [Article 1]. Describe the expenditures and epidemiological profile of patients that used medicines for the treatment of CHB in SUS (2000-2004) [Article 2]. Conduct a cost-effectiveness analysis in SUS perspective comparing interferon (conventional and pegylated) with lamivudine in patients with HBC, elevated aminotransferase levels and no evidence of cirrhosis [Article 3]. Methods: Search mainly databases MEDLINE (Pubmed) and LatinAmerican and Caribbean Health Sciences (LILACS), from January 1970 to December 2007. The outcomes were virological, biochemical and histological response, seroconversion/response and adverse effects. To evaluate the methodological quality of the studies it was utilized the modified JADAD scale. A historical cohort of individuals with diagnosis of CHB in the beginning of the treatment identified from deterministic/probabilistic linkage from SUS outpatient information data system (2000- 2004). To describe patients profile it were considered gender, age, residence region at baseline, year of treatment initiation, diagnosis at the beginning of the treatment and treatment regimens. The average and median expenditure (R$) per year of follow-up and total expenses were updated to December/2008 based on National consumer Prices Index. To see differences in expenses according to the diagnosis at the beginning of the treatment, Friedman test was used, between independent groups Kruskal-Wallis test and Spearman correlation by age. It was considered a 5% level of significance. A cost-effectiveness analysis was conducted in SUS perspective comparing interferon (conventional and pegylated) with lamivudine for the treatment of CHB. A Markov model was developed for CHB with 40 years of follow up. Costs and benefits were discounted at 5%. Annual ratesof disease progression, costs due to complications and efficacy of the drugs were obtained from literature and utility measurements applying EuroQol (EQ 5D). One-way and probabilistic sensitivity analysis evaluated the uncertainties. Results: It was selected 35 articles: 18 of interferon alfa, three of pegylated interferon and 14 of lamivudine. Most studies showed moderate quality in the classification of modified JADAD scale. In cohort (2000-2004) it was analyzed 1570 patients with CHB B18.1 and 38.0% lived in Southeast, majority were male aged 41-50 years. Higher median expenditures occurred in the first year of follow-up, for those with continued use of interferon or lamivudine or who started treatment with interferon. In cost-effectiveness analysis for HBeAg positive patients, pegylated interferon exhibited more benefits in health but cost-effectiveness ratio above the threshold acceptable in Brazil. For HBeAg negative patients interferon showed more benefits in health at an favorable cost-effectiveness threshold. Conclusions: Peginterferon demonstrated superior efficacy to interferon and lamivudina, not statistically significant and similar side effects to interferon. Lamivudine has the advantage of being sensitive to virus in patients HBeAg negative and showed development of resistance. In the cohort (2000-2004) expenditures on medicines were considered high in SUS. Interferon could be considered the chosen alternative in health care systems with limited resources